The Academic Skills Handbook : Your Guide to Success in Writing, Thinking and Communicating at University. - Hopkins, Diana (Sage, 2024)
This is your complete guide to acing your assignments and getting the most out of your time at university. Packed with tips, tools and a digital companion loaded with real-life examples, this book will help you: